Alternative splicing of viral transcripts: the dark side of HBV. Issue 12 (17th September 2021) - Kremsdorf, Dina; Lekbaby, Bouchra; Bablon, Pierre; Sotty, Jules; Augustin, Jérémy; Schnuriger, Aurélie; Pol, Jonathan; Soussan, Patrick
Abstract : Regulation of alternative splicing is one of the most efficient mechanisms to enlarge the proteomic diversity in eukaryotic organisms. Many viruses hijack the splicing machinery following infection to accomplish their replication cycle. Regarding the HBV, numerous reports have described alternative splicing events of the long viral transcript (pregenomic RNA), which also acts as a template for viral genome replication. Alternative splicing of HBV pregenomic RNAs allows the synthesis of at least 20 spliced variants. In addition, almost all these spliced forms give rise to defective particles, detected in the blood of infected patients. HBV-spliced RNAs have long been unconsidered, probably due to their uneasy detection in comparison to unspliced forms as well as for their dispensable role during viral replication. However, recent data highlighted the relevance of these HBV-spliced variants through (1) the trans-regulation of the alternative splicing of viral transcripts along the course of liver disease; (2) the ability to generate defective particle formation, putative biomarker of the liver disease progression; (3) modulation of viral replication; and (4) their intrinsic propensity to encode for novel viral proteins involved in liver pathogenesis and immune response. Altogether, tricky regulation of HBV alternative splicing may contribute to modulate multiple viral and cellular processes all along the course of HBV-related liver disease.